2019
DOI: 10.1038/s41598-019-48893-9
|View full text |Cite
|
Sign up to set email alerts
|

Evolution, dynamic expression changes and regulatory characteristics of gene families involved in the glycerophosphate pathway of triglyceride synthesis in chicken (Gallus gallus)

Abstract: It is well documented that four gene families, including the glycerophosphate acyltransferases (GPATs), acylglycerophosphate acyltransferases (AGPATs), lipid phosphate phosphohydrolases (LPINs) and diacylglycerol acyltransferases (DGATs), are involved in the glycerophosphate pathway of de novo triglyceride (TG) biosynthesis in mammals. However, no systematic analysis has been conducted to characterize the gene families in poultry. In this study, the sequences of gene family members in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Genes involved in this lipid synthesis process, including ELOVL6 related to fatty acids and SQLE related to cholesterol, were upregulated by estrogen at the genome level, while estrogen repressed the expression of gga-miR-221-5p, which was proved by in vitro and in vivo trial. Moreover, we found that the TG and TC contents were also dramatically increased under the estrogen treatment in chicken [47], and our results were consistent with previous studies [48]. Meanwhile, it is well known that liver X receptor alpha (LXR-α) is also an important regulators of liver lipid metabolism.…”
Section: Discussionsupporting
confidence: 92%
“…Genes involved in this lipid synthesis process, including ELOVL6 related to fatty acids and SQLE related to cholesterol, were upregulated by estrogen at the genome level, while estrogen repressed the expression of gga-miR-221-5p, which was proved by in vitro and in vivo trial. Moreover, we found that the TG and TC contents were also dramatically increased under the estrogen treatment in chicken [47], and our results were consistent with previous studies [48]. Meanwhile, it is well known that liver X receptor alpha (LXR-α) is also an important regulators of liver lipid metabolism.…”
Section: Discussionsupporting
confidence: 92%
“…The blood plasma biochemical index of associated with lipid synthesis and metabolism mainly include triglyceride (TG), low-density lipoprotein cholesterol (LDL-c), high-density lipoprotein cholesterol (HDL-c), total cholesterol (TC) and very low-density lipoprotein cholesterol (VLDL-c) [ 25 , 28 ]. Among them, the cotent of first four index in serum samples were detected using a blood analyzer (Hitachi 7100), while the cotent of VLDL-c was indirectly calculated by the Friedewald formula: VLDL-c = TC-HDL-c-LDL-c [ 26 , 27 , 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, estrogen, as an important inducer of certain liver genes, rises significantly in the sexually mature hens compared to the sexually immature hens [ 23 ]. And most of those estrogen-induced genes involve in hepatic fatty acid synthesis and the assembly of triglyceride-rich lipoprotein particles to lead to hypersecretion of these lipoproteins into the circulation [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…As reported previously, orthologous genes might be differentiated from a common ancestral gene ( Yang et al, 2019 ). To further evaluate the evolutionary relationships between EBP / EBP-like in different species, here, a rooted evolutionary time tree was constructed with zebrafish EBP served as an outgroup sequence.…”
Section: Discussionmentioning
confidence: 60%
“…The reliability of the tree was assessed using 1,000 bootstrap replicates. The numbers at each clade represent bootstrap support values were given as percentages ( Tian et al, 2018 ; Yang et al, 2019 ). Percentage amino acid sequence identity and sequence similarity were determined using the BLOSUM62 matrix algorithm ( Styczynski et al, 2008 ).…”
Section: Methodsmentioning
confidence: 99%